Retrievals of chlorine chemistry kinetic parameters from Antarctic ClO microwave radiometer measurements - S. Kremser; R. Schofield; G. E. Bodeker; B. J. Connor; M. Rex; J. Barret; T. Mooney; R. J. Salawitch; T. Canty; K. Frieler; M. P. Chipperfield; U. Langematz; et al. (Atmospheric Chemistry and Physics, 2011)
Key kinetic parameters governing the partitioning of chlorine species in the Antarctic polar stratosphere were retrieved from 28 days of chlorine monoxide (ClO) microwave radiometer measurements made during the late winter/early spring of 2005 at Scott Base (77.85° S, 166.75° E). During day-time the loss of the ClO dimer chlorine peroxide (ClOOCl) occurs mainly by photolysis. Some time after sunrise, a photochemical equilibrium is established and the ClO/ClOOCl partitioning is determined by the ratio of the photolysis frequency, J , and the dimer formation rate, k f . The values of J and k f from laboratory studies remain uncertain to a considerable extent, and as a complement to these ongoing studies, the goal of this work is to provide a constraint on that uncertainty based on observations of ClO profiles in the Antarctic. First an optimal estimation technique was used to derive J / k f ratios for a range of K eq values. The optimal estimation forward model was a photochemical box model that takes J , k f , and K eq as inputs, together with a priori profiles of activated chlorine (ClO x = ClO+2×ClOOCl), profiles of ozone, temperature, and pressure. JPL06 kinetics are used as a priori in the optimal estimation and for all other chemistry in the forward model. Using the more recent JPL09 kinetics results in insignificant differences in the retrieved value of J /k f . A complementary approach was used to derive the optimal kinetic parameters; the full parameter space of J , k f , K eq and ClO x was sampled to find the minimum in differences between measured and modelled ClO profiles. Furthermore, values of K eq up to 2.0 times larger than recommended by JPL06 were explored to test the sensitivity of the J / k f ratio to changes in K eq . The results show that the retrieved J / k f ratios bracket the range of 1.23 to 1.97 times the J / k f value recommended by JPL06 over the range of K eq values considered. The retrieved J / k f ratios lie in the lower half of the large uncertainty range of J / k f recommended by ...